A perspective on the symptoms and causes of the financial crisis - Cabral, Ricardo (Journal of Banking & Finance, 2013)
Prior to the 2007–2008 financial crisis, banking sector profits were very high but the profitability of financial intermediation was poor. Using a novel model of banking, this article argues that the high profits were achieved through balance sheet expansion and growing default, liquidity, and term risk mismatches between assets and liabilities. As a result, large banks’ financial leverage rose as they became less liquid, setting the conditions for a systemic banking crisis. This article argues that the increase in financial leverage was possible due to misguided changes in the regulatory framework, specifically, the Basel I capital accord and reductions in reserve requirements. Finally, this article overviews and assesses the policy response in the aftermath of the crisis.